The Second Checklist of Bryobionta of Ukraine (CHORNOMORSKI BOTANICAL JOURNAL, 2014)
The second checklist of bryophythes of Ukraine is given according to the contemporary taxonomical system in this edition (Checklist first published in 2008). The bryophytes (superdivision Bryobionta) refer to 3 divisions: Anthocerotophyta (4 species), Marchantiophyta (192 species), Bryophyta (653 species). Species are placed alphabetically. Modern Latin names and known synonyms are given to each species. Literature sources on the Ukrainian bryoflora, including those published long ago as well as of the latest decades, especially generalized works, are quoted here. Distribution of all the species both in physiogeographic plains zones and mountain landscapes: zone of mixed coniferousdeciduous forests (Ukraine Polissja), zone of deciduous forests (nemoral zone), the Foreststeppe zone, the Steppe zone (with steppe Crimea), Carpathian mountain region, Crimean mountain region and administrative regions of Ukraine is shown. The indications about species which were not presented in the first Ukrainian Checklist of Briobionta (2008), questionable species and species that were excluded from Ukrainian bryoflora are given.
Keywords: Bryobionta, Anthocerotophyta, Marchantiophyta, Bryophyta, Checklist, Ukraine.